THE INFLUENCE OF HUMAN RESOURCE ACCOUNTING ON FINANCIAL REPORTING TRANSPARENCY AND INVESTOR TRUST AT PT CITRA MEDIKA SIDOARJO - Sadiqin, Amin; Arvita, Rizki; Yuli Susanti, Evi (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the influence of Human Resource Accounting on Transparency of Financial Reporting and Investor Trust at PT Citra Medika Sidoarjo, that places human resources as a strategic asset of the company, so it is expected to be able to improve the quality of financial information and strengthen investor trust. This study uses a quantitative method with an associative approach. The data used are primary data obtained through distributing questionnaires to respondents related to the management and understanding of the company's financial reporting. Data analysis techniques were carried out using IBM SPSS, including validity tests, reliability tests, classical assumption tests, linear regression analysis, t-tests, F-tests, and coefficient of determination (R²) tests. The results of the study indicate that Human Resource Accounting has a positive and significant effect on Transparency of Financial Reporting, it’s also proven to have a positive and significant effect on Investor Trust. This study provides implications that the optimal implementation of Human Resource Accounting can increase the transparency of financial reporting and strengthen investor confidence, especially in health service companies such as PT Citra Medika Sidoarjo.